Knowledge and practice towards childhood immunization among parents in Rompin, Pahang, Malaysia - Lee, Siew Pien; Mohd Arifin, Siti Roshaidai; Mohd Razali, Rossheilawani; Makhdzir, Norafisyah (Innovare Academics Sciences, 2020)
The childhood immunization can be considered as mortality prevention during the last decades particularly among children under 5 years of age. As the primary health decision makers for their children, the knowledge and practice of parents towards immunization is essential for immunization commitment and timeliness. The aim of this study was to determine the knowledge, and practices of parents regarding childhood immunization. Materials and Methods: A cross-sectional descriptive study was conducted among parents in Rompin, Pahang, Malaysia. A set of self-administered questionnaires consisted of 20 questions was used to examine the level of knowledge and level of practice on childhood immunization among 153 parents. The descriptive analysis was shown percentages and frequencies. The association between the level of knowledge and practice on childhood immunization of parents was analysed using chi-square and fisher‟s exact test, p<0.05 was considered as statistically significant. Results: Out of 153 parents surveyed, 82 (53.6%) parents have high level of knowledge and 111(72.5%) parents have a good practice on childhood immunization. The parents‟ total knowledge score was positively associated with the total practice score towards childhood immunisation (X2=0.84, P< 0.001). Conclusion: Although parents had adequate knowledge and practice on some aspects regarding childhood immunization, gaps were identified. There is a need for educational interventions to upgrade parents‟ knowledge especially for resident of rural areas.